Plant foods in the Late Palaeolithic of Southern Italy and Sicily: Integrating carpological and dental calculus evidence. (20th April 2023) - Carra, Marialetizia; Zupancich, Andrea; Fiorin, Elena; Sarti, Lucia; Lo Vetro, Domenico; Martini, Fabio; Cristiani, Emanuela
Abstract: Several caves from Southern Italy and Sicily provided invaluable evidence, including several human burials, for reconstructing human adaptations and subsistence in the area during the Upper Palaeolithic. A wealth of information is available concerning the exploitation of animal resources as food. However, little is still known about the role of plants in the diet of the ancient hunter-gatherers of the region. By combining the carpological data with vegetal micro-debris entrapped in human dental calculus, we provide new clues about the dietary role of plant foods in the analysed area during the Late Glacial. Our study focused on five key sites from Southern Italy and Sicily: Grotta della Serratura in Campania, Grotta del Romito in Calabria, Grotta del Cavallo in Apulia, Grotta di San Teodoro and Grotta d'Oriente in Sicily. Our results demonstrate that several plant resources were exploited at these sites, including seeds, grasses, and fruits. Amongst the carpological remains recovered, several plant taxa are known for their medical properties. Overall, our study explores how critical climatic and environmental changes characterising the timeframe between the end of the Last Glacial Maximum and the beginning of the Holocene affected Late Upper Palaeolithic dietary habits. Moreover, it shows the methodological relevance of combining different strands of archaeological evidence for reconstructing the Palaeolithic diet.